Microbial Transformation of Hesperidin and Biological Evaluation - Kirci, Damla; Demirci, Fatih; Demirci, Betul (Amer Chemical Soc, 2023)
The main aim of the study was the biotransformation evaluation of hesperidin for functionalization by 25 different nonhuman pathogenic microorganisms. As a result, four metabolites were identified and characterized. The structure of pinocembrin and naringenin from the microbial transformation of hesperidin was determined initially with LC/MS-MS. The metabolites eriodictyol and hesperetin were isolated, and their molecular structure was determined by NMR and MS. Pinocembrin, eriodictyol, and naringenin were characterized as new hesperidin microbial transformation metabolites, to the best of our knowledge. In order to evaluate the bioactivity, in vitro 5-lipoxygenase (5-LOX) enzyme inhibition, antioxidant, antimicrobial, and acute toxicity evaluations using the brine shrimp assay of hesperidin and its metabolites were performed comparatively. According to antioxidant and anti-inflammatory activity results, hesperetin metabolite was more active than naringenin and hesperidin. The antimicrobial activity of hesperetin and naringenin against the human pathogenic Staphylococcus aureus strain was relatively higher when compared with the substrate hesperidin. In line with this result, biofilm activity of hesperetin and naringenin against S. aureus with combination studies using biofilm formation methods was carried out. The checkerboard combination method was utilized for biofilm layering, also for the first time in the present study. As an initial result, it was observed that hesperidin and naringenin exerted a synergistic activity with a fractional inhibitory concentration index (FICI) value of 1.063. Considering the bioactivity of hesperidin, hesperetin, and naringenin used as substrates are relatively nontoxic. The microbial and enzymatic biotransformation of natural products such as hesperetin and its new bioactive metabolites still have pharmacological potential, which needs further experimentation at the molecular level..
Keywords: Citrus Flavonoids; Biofilm Formation; Biotransformation; Antioxidant; Combination; Naringenin; Hesperetin; Mechanisms; Flavanones; Extract